2012
DOI: 10.1021/je201044n
|View full text |Cite
|
Sign up to set email alerts
|

Isopiestic Measurement and Solubility Evaluation of the Ternary System LiCl–SrCl2–H2O at 298.15 K

Abstract: Water activity in the ternary system LiCl–SrCl2–H2O and its sub-binary systems has been elaborately measured by the isopiestic method. The measured water activities were used to justify the reliability of solubility isotherms reported in literature by correlating them with two thermodynamic models, that is, the extended Pitzer model and the Pitzer–Simonson–Clegg model. It was found that the extended Pitzer model cannot correlate consistently the water activities measured and either set of the solubility isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…It can be seen from Table 6, Figures 6 and 7 13 298, 14,15 and 308 K, 16,33 it is found that this ternary system contains two invariant points, there is no formation of double salt or solid solution, strontium chloride exists in the form of hexahydrate and dihydrate, while only some solubility data were given without the values at the invariant point in the literature 33 under the condition around 308 K. The ternary system LiCl− NaCl−H 2 O has been reported from 273 to 348 K, [17][18][19][20]34 the results show that the system is a simple saturation system with only one invariant point at these temperatures, and lithium chloride exists in the form of LiCl O has the highest solubility in this system and is the most difficult to crystallize and separate from the saturated solution, and the crystallization field of NaCl is the largest, so NaCl is most readily precipitated from the mix solution. In addition, when lithium chloride is added to the cosaturated solution of sodium chloride and strontium chloride, the composition of sodium chloride and strontium chloride in the liquid phase decreases with the increase of lithium chloride, which indicates that lithium chloride has a strong salting-out effect on strontium chloride and sodium chloride.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It can be seen from Table 6, Figures 6 and 7 13 298, 14,15 and 308 K, 16,33 it is found that this ternary system contains two invariant points, there is no formation of double salt or solid solution, strontium chloride exists in the form of hexahydrate and dihydrate, while only some solubility data were given without the values at the invariant point in the literature 33 under the condition around 308 K. The ternary system LiCl− NaCl−H 2 O has been reported from 273 to 348 K, [17][18][19][20]34 the results show that the system is a simple saturation system with only one invariant point at these temperatures, and lithium chloride exists in the form of LiCl O has the highest solubility in this system and is the most difficult to crystallize and separate from the saturated solution, and the crystallization field of NaCl is the largest, so NaCl is most readily precipitated from the mix solution. In addition, when lithium chloride is added to the cosaturated solution of sodium chloride and strontium chloride, the composition of sodium chloride and strontium chloride in the liquid phase decreases with the increase of lithium chloride, which indicates that lithium chloride has a strong salting-out effect on strontium chloride and sodium chloride.…”
Section: Resultsmentioning
confidence: 83%
“…There is only the crystallization field of strontium chloride hexahydrate in solid phases without that of strontium chloride dihydrate, and SrCl 2 has an obvious salting-out effect on NaCl and KCl. The quaternary system NaCl−KCl−SrCl 2 −H 2 O has been calculated from 273 to 373 K 12 with Pitzer model as well as the ternary system LiCl−SrCl 2 −H 2 O at 273, 13 298, 14,15 and 308 K 16 and the ternary system LiCl−NaCl−H 2 O from 273 to 348 K. 17−20 In addition, the solubilities of the quinary system LiCl−NaCl−KCl−SrCl 2 −H 2 O were predicted by using the Pitzer thermodynamic model at 298.15 K. 21,22 These data could provide a theoretical reference for the comprehensive development and utilization of brine resources containing strontium and lithium.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [5] were determined osmotic coefficients of the Li 2 SO 4 -H 2 O (concentration from 0.2 to 8.7 mol·kg -1 ), MgSO 4 -H 2 O (concentration from 0.6 to 12.7 mol·kg -1 ) and Li 2 SO 4 -MgSO 4 -H 2 O mixing system (ionic strength from 1.4 to 13.5 mol·kg -1 ) and have verified the applicability of Pitzer equation and Scatchard equation for this system. Guo [6] et al used isopiestic equipment were measured water activity of the LiCl-SrCl 2 -H 2 O system. Li [7] by using improved isopiestic apparatus were determined water activity and osmotic coefficients of LiCl-H 2 O (concentration from 0.5 to 9.2 mol·kg -1 ), Li 2 SO 4 -H 2 O (concentration from 0.3 to 2.5 mol·kg -1 ) and LiCl-Li 2 SO 4 -H 2 O (ionic strength from 0.5 to 9.5 mol·kg -1 ) at 273.15 K, based on Pitzer ion interaction model and analyzed the experimental data, fitting Pitzer parameters under this temperature and modified and extended the rules of Zdanovskii, so that it can better describe the mixed system.…”
Section: Thermodynamic Properties Of Aqueous Solutions Containing Litmentioning
confidence: 99%
“…For the complex oilfield brine system, many subsystems have been studied in the literature. It is worth noting that Sr and Ca can easily form the solid solution (Ca, Sr)­Cl 2 ·6H 2 O in the system. Therefore, separation of Sr from the brine needs to avoid generating the solid solution.…”
Section: Introductionmentioning
confidence: 99%
“…For the quaternary system (NaCl + CaCl 2 + SrCl 2 + H 2 O) at 288.15 K, the minerals correspond to the solid solution (Ca, Sr)­Cl 2 ·6H 2 O, minerals CaCl 2 ·6H 2 O, SrCl 2 ·6H 2 O, and NaCl. Meanwhile, the system containing Sr 2+ , K + , Na + , and Cl – between 291.15 and 387.15 K and the system (LiCl + KCl/CaCl + SrCl 2 + H 2 O) at 308 K were determined. , The solubility, water activity, and thermodynamic model of the system (LiCl + SrCl 2 + H 2 O) at 273.15 and 298.15 K were determined. …”
Section: Introductionmentioning
confidence: 99%